2023
DOI: 10.1161/circulationaha.122.063444
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type 2 Diabetes and Changes in Myocardial Structure, Contractile Function, Energetics, and Blood Flow Before and After Aortic Valve Replacement in Patients With Severe Aortic Stenosis

Nicholas Jex,
John P. Greenwood,
Richard M. Cubbon
et al.

Abstract: BACKGROUND: Type 2 diabetes (T2D) is associated with an increased risk of left ventricular dysfunction after aortic valve replacement (AVR) in patients with severe aortic stenosis (AS). Persistent impairments in myocardial energetics and myocardial blood flow (MBF) may underpin this observation. Using phosphorus magnetic resonance spectroscopy and cardiovascular magnetic resonance, this study tested the hypothesis that patients with severe AS and T2D (AS-T2D) would have impaired myocardial energeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We also show that T2DM is independently associated with outcome, its importance more apparent for CV mortality in the subgroup undergoing SAVR (I i for T2DM of 14%, greater than age). T2DM is known to be associated with an increased risk of heart failure, persistent impairment of myocardial energetics, and myocardial perfusion after AVR; 8 dedicated trials of novel diabetic medications in this patient group should therefore be considered. We have previously shown that female sex was associated with CV mortality; 4 this effect remains significant with extended follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We also show that T2DM is independently associated with outcome, its importance more apparent for CV mortality in the subgroup undergoing SAVR (I i for T2DM of 14%, greater than age). T2DM is known to be associated with an increased risk of heart failure, persistent impairment of myocardial energetics, and myocardial perfusion after AVR; 8 dedicated trials of novel diabetic medications in this patient group should therefore be considered. We have previously shown that female sex was associated with CV mortality; 4 this effect remains significant with extended follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of AS, an association between altered myocardial energetics, i.e. reduced PCr/ATP ratios, and contractile dysfunction have been reported in T2D patients [ 17 , 38 , 39 ] . However, the underlying molecular mechanisms leading to this reduced ATP production in the human diabetic heart under chronic pressure overload remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…At pre-clinical level, we reported that insulin resistance induced by a high-fat diet in mice worsened survival, cardiac hypertrophy and systolic/diastolic dysfunction under aortic constriction [ 16 ]. In patients with AS, T2D has been associated to a higher cardiomyocyte resting tension, an increased vascular advanced glycation end product deposition [ 14 ], an impaired myocardial energetics as reflected by the reduced phosphocreatine to ATP ratio [ 17 ], oxidative stress and metabolic dysfunction [ 18 ]. Altogether, these data suggest a strong role for metabolic alterations in the deleterious effect of T2D on LV remodeling and function in patients with severe AS.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have been performed in highly selective, homogenous, patient groups, but energetic changes also occur in many morbidities that are associated with increased risk of developing heart failure. For example, PCr/ATP is reduced in LVH [ 87 ], atrial fibrillation [ 107 ], aortic stenosis [ 108 ], obesity [ 109 , 110 ] and in Type 2 diabetes [ 111 , 112 ]. In one notable preclinical study, it was found that diabetic mice were relatively protected from heart failure induced by pressure overload and this was attributed to restoring flexibility in energy substrate utilisation [ 113 ].…”
Section: Cardiac Energetics In Chronic Heart Failurementioning
confidence: 99%